DEPRESSION OF PARENTS OF CHILDREN WITH SURVIVORS LEUKEMIA - Ramdhanie, Gusgus Ghraha; Nugraha, Bambang Aditya; Sulastini, Sulastini (Jurnal Medika Cendikia, 2024)
Parents faced with a diagnosis of leukemia in a child may manifest depressive symptoms. The long treatment process for children with leukemia is a major source of stress for parents that affects mental health. The purpose of this study is to identify the level of depression in parents who have children with leukemia. This study used a quantitative descriptive design with a non-probability sampling technique of accidental sampling type, involving 23 parents. The instrument used was the Beck Depression Inventory II (BDI-II). The data analysis used was univariate. The results showed that parents were not depressed (39%), mild depression (22%), moderate depression (26%), and severe depression (13%). The data showed that the most common symptoms of depression experienced by parents were sadness (57%), feeling worthless (48%), fatigue (52%), and loss of sexual desire (52%). This study is expected to help other researchers develop research on similar topics.